Cyber Learning: Ikhtiar Baru Dunia Pendidikan di Masa Pandemi Covid-19 - Wahyudi, Dedi; Kurniasih, Novita; Prasetyo, Yusuf Dwi (Tapis: Jurnal Penelitian Ilmiah, 2021)
The Covid-19 virus, which is endemic throughout the world, is no exception to the government's proximity to making home study policies in the realm of education. All levels of education starting from the lowest level such as early childhood education to the university level carry out their knowledge through Cyber Learning. In today's era of crisis, it is difficult to enjoy virtual learning. Various platforms from around the world provide internet-based education services or CyberLearning free. This paper uses a library research method with data sources obtained from various credible written sources. Careful preparation is required to be able to carry out Cyber Learning-based learning for both educators and students so that learning can run smoothly. Whatsapp, Google Classroom, Zoom, and Schoology are some examples of Cyber Learning that can be used easily for educators and students.